1974
DOI: 10.1113/jphysiol.1974.sp010427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thymol on the electrical and mechanical properties of the guinea‐pig taenia coli

Abstract: SUMMARYEffects of thymol (0.02-2 mM) on the electrical and mechanical activities of the smooth muscle cells of the guinea-pig taenia coli were investigated with either micro-electrode or double sucrose gap methods.1. Thymol, in a concentration of more than 0 03 mM, reduced the amplitude and maximum rate of rise of the spikes without any change of the membrane potential. When the concentration was increased to 0 3 mm, thymol completely blocked the spontaneous and evoked spike activities. In a concentration of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Control curve+Origanum (116) 2 ml Control curve+Thymol 9 x 10-5 M ITO and KURIYAMA [21,22] propose that thymol acts on either the phospholipid layer o r the protein layer of the plasma membrane, inhibiting the Ca2+ influx across the membrane and producing immobilisation of the sequestered Ca2+ in the cell. Our results are in good agreement with this hypothesis.…”
Section: Control Curve Camentioning
confidence: 99%
“…Control curve+Origanum (116) 2 ml Control curve+Thymol 9 x 10-5 M ITO and KURIYAMA [21,22] propose that thymol acts on either the phospholipid layer o r the protein layer of the plasma membrane, inhibiting the Ca2+ influx across the membrane and producing immobilisation of the sequestered Ca2+ in the cell. Our results are in good agreement with this hypothesis.…”
Section: Control Curve Camentioning
confidence: 99%
“…Thymol (<0.05 mM) suppressed the action potential and reduced membrane resistance and potential in the stomach of guinea pigs at higher concentrations. Thymol (1 mM) inhibited the generation of spikes, hyperpolarized the membrane and resistance in the rectum and ileum ( Ito and Kuriyama, 1974 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thymol mechanisms of action are not completely defined or understood; however, some authors have proposed hypotheses about its influence on smooth muscle relaxation ranging from calcium channel blockade to concentration-dependent inhibition of muscarinic Ach receptors. 34,36,43 Nevertheless, results of the study demonstrated that thymol micro concentrations reduce Ca 2+-ATPase activity and increase Ca 2+ permeability in the sarcoplasmic membrane; on the other hand, they show that this compound exerts an agonists effect on α1, α2, and β adrenergic receptors in guinea pig portal vein and stomach isolated tissue producing a relaxing effect on them, these results suggest that the molecule's action mechanism differs depending on smooth muscle type. 41 The evidence to understand thymol's action mechanism on smooth tissue is scarce, so these mechanisms have been investigated in different tissues or cell lines.…”
Section: Thymol Mechanisms Of Actionmentioning
confidence: 89%
“…35 Also, different concentrations of thymol effects (0.02-2 mM) electrical and mechanic activities of guinea pig Taenia coli smooth muscle cells found that thymol at 0.05 mM suppresses the membrane's action potential and reduces its resistance and potential; likewise, 1mM concentration inhibits spike generations, hyperpolarizes membrane and its resistance. 36 On the other hand, the antispasmodic activity of thymol was analyzed in rabbit jejunum in order to know if it is possible to use this compound to relieve irritable bowel discomfort; the results of this experiment showed that it does have an inhibitory effect on contraction (IC50 2.85 × 10 -2 ± 1.2 × 10 -2 µg/mL). 37 It is worth mentioning that the result rules out that the mechanism of action of thymol in intestinal tissue is by activation of the β2-adrenergic receptors present in this tissue.…”
Section: Antispasmodic Effect On Gastrointestinal Smooth Muscle Tissuementioning
confidence: 99%